Impact of supermarkets and fast–food chains on horticulture supply chains in Argentina - Ghezan, Graciela Susana; Mateos, Mónica; Viteri, Maria Laura (Wiley, 2024)
In the 1990s, the supermarket and fast–food sectors grew rapidly in Argentina. Both were dominated by multinational firms, and their growth drove profound change in food market systems and farming. This article analyses the impact of this development on fruit and vegetables supply chains, in particular the way the advent of McDonald’s affected the supply chain for frozen French fried potatoes. It shows that there is a tendency for such changes to favour medium and large producers, with evidence of the exclusion of small farmers.